Fabrication of Multi-Layered Microspheres Based on Phase Separation for Drug Delivery - He Xia (Micromachines, 2021)
In this work, we used a co-flow microfluidic device with an injection and a collection tube to generate droplets with different layers due to phase separation. The phase separation system consisted of poly(ethylene glycol) diacrylate 700 (PEGDA 700), PEGDA 250, and sodium alginate aqueous solution. When the mixture droplets formed in the outer phase, PEGDA 700 in the droplets would transfer into the outer aqueous solution, while PEGDA 250 still stayed in the initial droplet, breaking the miscibility equilibrium of the mixture and triggering the phase separation. As the phase separation proceeded, new cores emerged in the droplets, gradually forming the second and third layers. Emulsion droplets with different layers were polymerized under ultraviolet (UV) irradiation at different stages of phase separation to obtain microspheres. Microspheres with different layers showed various release behaviors in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). The release rate decreased with the increase in the number of layers, which showed a potential application in sustained drug release.